Online peer learning amid Covid-19 pandemic in Malaysian higher learning institution - Krishnan, Shartini Devi; C. Hassan, Norlizah (Karadeniz Technical University, 2021)
Online learning has been a tremendous influence on helping people in promoting potential abilities during Covid-19 pandemic where all learning institutions were closed and adapted blended learning as an alternative due to Movement Control Order (MCO). In this respect, learning via social media such as WhatsApp, Facebook, and YouTube have become an emerging phenomenon in students’ academic achievements. Therefore, this study has been conducted to identify the level of UPM undergraduates’ cognitive engagement, motivation and emotional engagement while practicing Online Learning via social media. This study aims to determine the relationships between online peer learning and academic achievements, and the differences between genders in academic achievements. The study was based on the quantitative method in nature with correlational design using questionnaires. Cluster sampling techniques applied and a total of 225 responses were collected. Result indicated highly perceived mean score on engagement of undergraduates’ use the social media for learning purposes. There is a positive correlation between online peer learning and undergraduates’ academic achievement. The T-Test analysis revealed that there is a significant different between gender in academic achievement and female undergraduates had the highest mean score. The findings illustrate undergraduates’ emotional engagement appears as an essential aspect in their learning process. Students keen to participate in online learning which makes them feel comfortable and positive when they engaged in online social interactions. The Ministry of Education should take proactive measure to promote the use of online peer learning to encourage creative, innovative and practical based learning in higher institutions.